Adipokine dysregulation and adipose tissue inflammation in human obesity. (3rd August 2018) - Unamuno, Xabier; Gómez‐Ambrosi, Javier; Rodríguez, Amaia; Becerril, Sara; Frühbeck, Gema; Catalán, Victoria
Abstract: Obesity, a worldwide epidemic, confers increased risk for multiple serious conditions, including type 2 diabetes, cardiovascular diseases, nonalcoholic fatty liver disease and cancer. Adipose tissue is considered one of the largest endocrine organs in the body as well as an active tissue for cellular reactions and metabolic homeostasis rather than an inert tissue for energy storage. The functional pleiotropism of adipose tissue relies on its ability to synthesize and release a large number of hormones, cytokines, extracellular matrix proteins and growth and vasoactive factors, collectively termed adipokines that influence a variety of physiological and pathophysiological processes. In the obese state, excessive visceral fat accumulation causes adipose tissue dysfunctionality that strongly contributes to the onset of obesity‐related comorbidities. The mechanisms underlying adipose tissue dysfunction include adipocyte hypertrophy and hyperplasia, increased inflammation, impaired extracellular matrix remodelling and fibrosis together with an altered secretion of adipokines. This review describes how adipose tissue becomes inflamed in obesity and summarizes key players and molecular mechanisms involved in adipose inflammation.